ISLAMIC PARTIES AND THE POLITICS OF CONSTITUTIONALISM IN INDONESIA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2012)
This article examines the relationship between religion and the state in Indonesia by exploring how Islam is used by political parties to shape the politics. The study shows that Islamic politics is a complementary in both nationhood and statehood in Indonesia. From the early days of the new-born nation-state, Muslims in Indonesia had played significant role in shaping the nation; nonetheless, they have never dominated the political power. Fragmentation among Muslims themselves and internal political parties is among the reason why religious (Islamic) parties failed in bringing religious identity to the state arena. Political subordination-inclusion-ignorance-confrontation is the circular game that features Islamic politics in Indonesia. The debatable issue on shari‘ah law, which is frequently used by Islamic parties, always becomes the core problem of the relation between Islam and the state. Even though Islam has played an important role in colouring the Indonesian politics, its existence remains complementary.